Genetics and Omics Analysis of Autoimmune Skin Blistering Diseases - Olbrich, Michael; Künstner, Axel; Witte, Mareike; Busch, Hauke; Fähnrich, Anke (Frontiers in Immunology, 2019)
Autoimmune blistering diseases (AIBDs) of the skin are characterized by autoantibodies against different intra-/extracellular structures within the epidermis and at the basement membrane zone (BMZ). Binding of the antibodies to their target antigen leads to inflammation at the respective binding site and degradation of these structures, resulting in the separation of the affected skin layers. Clinically, blistering, erythema and lesions of the skin and/or mucous membranes can be observed. Based on the localization of the autoantigen, AIBDs can be devided into pemphigus (intra-epidermal blistering diseases) and pemphigoid diseases (sub-epidermal blistering diseases), respectively. Although the autoantigens have been extensively characterized, the underlying causes triggering the diseases are still poorly understood. Besides the environment, genetic factors seem to play an important role in predisposing to AIBDs. Here, we review currently known genetic and immunological mechanisms that contribute to the pathogenesis of AIBDs. Among the most commonly encountered genetic predispositions for AIBDs are the HLA gene region, and deleterious mutations of key genes for the immune system. Particularly, HLA class II genes such as the HLA-DR and HLA-DQ alleles have been shown to be prevalent in patients. This prompts further epidemiological studies as well as unbiased Omics approaches on the transcriptome, microbiome and proteome level to elucidate common and private genetic risk factors and the molecular pathways leading to the pathogenesis of AIBDs.